"Desoxy-D2PM" from the Detection to Legal Control Measure - รัตนานุกูล , ภณิดา (Journal of Health Science of Thailand, 2021)
Adulteration of psychotropic substances that reduce appetite activity in weight loss supplement cause danger to consumer health. This practice is considered deceptive and illegal; therefore, the smuggling use of new synthetic substances that has not yet announced legal control can be found. In September 2017, Regional Medical Sciences Center 10 Ubon Ratchathani detected adulteration of 2-Diphenylmethylpyrrolidine or Desoxy-D2PM, a psychotropic substance. Desoxy-D2PM has never been detected in the samples of weight loss supplements received from private customer for laboratory analysis. This substance has never been announced as control substance in Thailand. Initiating from Desoxy-D2PM detection report, Department of Medical Sciences expanded the sample testing for Desoxy-D2PM in other brands of weight loss supplement. In fiscal year 2018, Desoxy-D2PM was found in 6 products so this led into the consideration process of the relevant department at the national level. As a result, DesoxyD2PM was announced to be schedule I-psychotropic substances as Ministry of Public Health Notification title: specify substance in schedule I (issue II), announced on January 21 st, 2019. In spite of being only a routine service, laboratory analysis can be very useful tool as surveillance measure to prevent harm to social and economic in order not to expand into a difficult problem to solve and for rapid and efficient consumer health protection; if the analyst has sufficient responsibility and experience.